SOCIAL MEDIA AS A DOUBLE-EDGED SWORD (Analysis of the Impact on Adolescent Mental Health in Indonesia) - Maulana, Irfan; Anggraini Wati, Maya; Prasetyo Wibowo, Galih (Jurnal Multidisipliner Bharasa, 2024)
The digital age has brought a major transformation in social interaction, especially among teenagers, with social media playing a central role. This phenomenon raises important questions about the impact of social media on adolescent mental health. This study delves into both sides of the influence of social media, considering it a double-edged sword that has both positive and negative potential for adolescent mental health in Indonesia. Through a qualitative approach, the study explores adolescents' perceptions, experiences, and responses to various aspects of social media, including exposure to cyberbullying, peer pressure, and social expectations. In addition, this study also highlights coping strategies developed by adolescents in dealing with these negative impacts. Results show that although social media provides a platform for self-expression and social support, overexposure and uncritical use can lead to increased anxiety, depression, and body image disorders. The findings underscore the importance of digital literacy and proactive mental health coaching among adolescents, as well as the important role parents and educators play in monitoring social media use. The study offers new insights into the complex dynamics of social media's influence on adolescents and drives the development of policies and programs that support better mental health.